(3cfR GdObGFbs - (3YHO Gddg Hf CMeO Hf eMehO GdfSaj, CHh GdHQcGJ, MGaX GdOjf,J (B710 (3g` s ((3eMehO Hf CMeO GdYjfi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CYR GdYde ai GdCYUGQ , hCYdi MRHg ai GdCeUGQ deG QCjJ Gdgee eGFdI Edi GdeNJUQGJ , hGdWHGY QGZHI Yf GdeWhdGJ CQOJ Cf CdNU GdhGai HPcQ eG Ye hbhYg hcKQ hLhOg s
(3BNQgG (B:s
(3aGVQH SgGe cd hGQK ef GdJUMjM ai cd GdJQcI , Ke CbSe GdeHdZ Ydi GdJUMjM hef UGdM GdhQKI Ydi TF aGLYd cCf de jcf hCbSe Ydi SgGe ef Hbi eG Hbi hGdMeO ddg Ydi GdEJeGe s
(3cJHJ YfGhjjf GdCHhGH HGdeOGO GdCMeQs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B67 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B32s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B1 - (3U (B464 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1515s
Keywords: (3Gdabg GdESdGejs